MEASURES OF INDUSTRY AGGLOMERATION IN BRAZIL: A STUDY ADDRESSING NEIGHBORING EFFECTS - Vignandi, Rafaella Stradiotto; Parré, José Luiz; Guimarães, Paulo de Freitas (Análise Econômica, 2016)
This paper addresses the impact of including neighboring effects to analyze the concentration status of some manufacturing sectors across the Brazilian meso-regions from 1995 through 2010. The analysis of spatially weighted indices – namely – points to a likely deconcentration process in most sectors of the Brazilian manufacturing industry in the period under study. In contrast to spatially unweighted indices, spatially weighted concentration indices proved to be more robust for addressing neighboring effects in the analysis of the (de)concentration process of the Brazilian industry.